Artesunate-related fever and delayed hemolysis in a returning traveler. Issue 2 (2015) - Lahoud, Jacquelyn S.; Lahoud, Oscar B.; Lin, Yu Shia; Ghitan, Monica; Chapnick, Edward K.; Solomon, William B.; Kuhn-Basti, Margaret
Abstract: Malaria is a serious and sometimes fatal disease caused by an intraerythrocytic parasite, and is commonly seen in developing countries. Approximately 1500 cases of malaria are diagnosed in the United States each year, mostly in travelers and immigrants returning from endemic areas[1] . There are many different regimens used to treat malaria, some of which are not approved in the USA. The side effects of these medications may not be familiar to physicians in the USA. We report a case of a returning traveler from Nigeria presenting with fever and hemolytic anemia caused by a delayed response to artesunate given 3 weeks earlier while in Nigeria. To our knowledge, there are few cases reported in the United States of hemolytic anemia secondary to artesunate therapy[2] .